2022
DOI: 10.1080/21505594.2022.2060464
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of viral proteins: Implication in virus–host interaction and virulence

Abstract: Glycans are among the most important cell molecular components. However, given their structural diversity, their functions have not been fully explored. Glycosylation is a vital post-translational modification for various proteins. Many bacteria and viruses rely on N -linked and O-linked glycosylation to perform critical biological functions. The diverse functions of glycosylation on viral proteins during viral infections, including Dengue, Zika, influenza, and human immunodeficiency vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 158 publications
0
34
0
Order By: Relevance
“…We wondered whether a specific part of genomic viral RNA might play a role in attenuated replication of GUINEA-18 in vitro . The GUINEA-18 structural proteins with the N-glycosylated E protein may have an effect on virus binding efficiency in decreasing the host-cell susceptibility to viral infection (26,27). The importance of 5’ region of GUINEA-18 in viral attenuation was examined using GUINEA-18/MR766 5’region chimera in which the 5’NCR followed by the sequence coding for C, prM and E proteins of GUINEA-18 were replaced by the counterpart region of MR766 MC using genetic reverse experiments based on ISA method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We wondered whether a specific part of genomic viral RNA might play a role in attenuated replication of GUINEA-18 in vitro . The GUINEA-18 structural proteins with the N-glycosylated E protein may have an effect on virus binding efficiency in decreasing the host-cell susceptibility to viral infection (26,27). The importance of 5’ region of GUINEA-18 in viral attenuation was examined using GUINEA-18/MR766 5’region chimera in which the 5’NCR followed by the sequence coding for C, prM and E proteins of GUINEA-18 were replaced by the counterpart region of MR766 MC using genetic reverse experiments based on ISA method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[45] Recent studies have indicated that modifications to the glycosylation pattern of viral antigens can impact their interaction with antibodies and subsequently influence immune responses. [46,47] Nordén et al demonstrated that reducing interfering O-linked glycans on the gE protein of VZV could enhance its binding to IgG antibodies, potentially leading to improved immune recognition and response. [48] To investigate whether modifying the glycosylation pattern of VZV gE could induce stronger immune responses, three mRNA sequences were designed and synthesized.…”
Section: Removal Of Glycosylation Of Ge Results In Decreased Immune R...mentioning
confidence: 99%
“…Viruses are obligate intracellular infectious agents that exploit host machinery to modify their viral proteins for survival. One of the key modifications is protein glycosylation [ 32 ]. As the secreted viruses are restricted in semisolid medium, the plaque forming must rely on the virus mediated cell-cell membrane fusion, which could be affected by the glycosylation modifications of virus [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key modifications is protein glycosylation [ 32 ]. As the secreted viruses are restricted in semisolid medium, the plaque forming must rely on the virus mediated cell-cell membrane fusion, which could be affected by the glycosylation modifications of virus [ 32 ]. Therefore, we hypothesized that the glycosylation modifications level of intracranial origin DENV-2 were blocked after replication in Vero cells and caused limited cell_-cell membrane fusion in Vero cells.…”
Section: Discussionmentioning
confidence: 99%